Kin transfers as safety nets in response to idiosyncratic and correlated shocks - Herskowitz, Sylvan; Kleemans, Marieke; Pulido, Cristhian (International Food Policy Research Institute, 2021)
While formal insurance is widespread in much of the developed world, households in lower-income countries continue to rely heavily on informal risk-sharing networks when faced with unexpected shocks. Kin networks of non-coresident family members may play an important role by providing each other with informal social protection, sharing resources in response to correlated production shocks (rainfall) or idiosyncratic household shocks (sickness and death). Using detailed panel data from Indonesia, we examine how inter-household transfers within a household’s kin network respond to different types of shocks and whether they are able to reduce household vulnerability. We find that households are exposed to meaningful risk from variations in local rainfall in the form of both income and household consumption. Rainfall substantially increases both transfers sent and received by households, suggesting that household and local supply effects dominate demand effects resulting from rainfall fluctuation. Finally, we find modest evidence that transfers reduce vulnerability of consumption to rainfall fluctuations by up to 11%, but do not find strong evidence on the efficacy of formal social protection programs.